Digital Readiness Mahasiswa dalam Menghadapi Transformasi Pembelajaran Berbasis Artificial Intelligence: Studi Kasus pada Mahasiswa Program Studi Pendidikan Agama Islam - Lathifatur Rasyidah; Alfi Rahmi (YASIN, 2026)
Students’ digital readiness in facing the transformation of Artificial Intelligence (AI)-based learning has become a focus of various studies, but research that specifically discusses the digital readiness of students in the Islamic Religious Education Study Program in the context of AI implementation remains limited. This study aims to explore the digital readiness of students in the Islamic Religious Education Study Program in facing the transformation of AI-based learning. This study used a qualitative approach with a case study design, involving 12 informants selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and were then analyzed using thematic analysis through the stages of data condensation, data display, and conclusion drawing and verification. The results show that students have relatively good digital readiness, as indicated by their ability to use digital technology and various AI applications to support learning, their ability to adapt to learning transformation, and their awareness of the importance of using technology ethically. However, several challenges were still found, namely limitations in constructing effective prompts, difficulty verifying the accuracy of information, and the tendency of some students to depend on AI outputs. The conclusion of this study emphasizes that strengthening digital competence, AI literacy, and digital ethics is an important foundation for supporting learning transformation in higher education. These findings contribute to the development of the concept of digital readiness in the context of Islamic Religious Education and provide practical implications for universities in designing more targeted programs to strengthen students’ digital competence.